Attitude of Millennial’s of Bangalore towards Wine and Impact of Pairing Indian Wines with Indian Flavors of Food - Thaqseen Bhanu, M. Thashneem; Prasanna Kumar, J.P. (International Journal of Psychosocial Rehabilitation, 2024)
Karnataka, is a state in the southern part of India and a popular wine producing region of the country. It has 16 wineries producing different types of wines focusing on quality wine making. According to [1], majority of the people in the Karnataka prefer beer and spirits; wine was always the least consumed beverage. According to the Wine Board of Karnataka, the wine consumption has been increased to 178 lakh liter from 13.71 lakh liter in 2007. The reason for this growth in the industry was due to high level income, changing lifestyle and health benefits of wine [2]. In order to increase the future consumption and attract consumers who prefer spirits and beer towards wine, one of the ways is to educate them on wines through wine and food pairing sessions as wine tasting create an impact on the purchase behaviour of consumers [3]. This paper therefore aims to understand the perfect match and level of liking among customers in regards to pairing Indian wines with the flavors of Indian cuisine. The study involved 21 respondents from Bangalore who were between the age group of 21 – 25 years (Millennials) who tasted the wine and food and analysed the wine pairing. The study examined 4 Indian wines which varied in price, colour and brand, namely Brand A - Shiraz, Brand B - Shiraz, Brand A - Sauvignon Blanc and Brand B - Sauvignon Blanc along with Indian Foods Chicken Tikka and Palak Paneer. The findings of the study were: the customers showed high level of liking towards wine and food pairing of Shiraz with Chicken Tikka and Sauvignon Blanc with Palak Paneer, the statistical difference between control and treatment group proved the importance of training on wine tasting, the overall higher level of liking was identified with a lower priced brand which proves that even wine pairing enhances the taste of liking towards wine irrespective of the price and brand. The results of the study could not be generalized for the whole country or state as it only focused on one city and the study has involved only 21 respondents. A future study can be done with a greater number of respondents and involving different Indian wine varieties along with a 15 minute olfactory training session before tasting.